1997
DOI: 10.1021/om970591a
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mediated Organometallic Synthesis:  The Activating Role of Silica for a High-Yield Route to [H4Os4(CO)12] and [HOs3(CO)10Y] (Y = OH, OR, Cl, Br, I, O2CR, SCN) Clusters from [Os3(CO)12]

Abstract: Activation of [Os3(CO)12] by the silica surface via reaction with surface silanol groups provides a new convenient general approach to the selective, high-yield synthesis of various osmium carbonyl clusters such as [H4Os4(CO)12] and [HOs3(CO)10Y] (Y = a three-electron donor such as OH, OR, Cl, Br, I, O2CR, and SCN). These silica-mediated syntheses compare favorably with the more conventional syntheses in solution because (i) differently from other related intermediates used in solution, silica-anchored [HOs3(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…For the synthesis of triosmium-carboxylate clusters, the parent triosmium carbonyl cluster Os 3 (CO) 12 , 1a, is of limited utility as it is rather inert; often an activated derivative such as Os 3 (CO) 10 (NCMe), 2a, Os 3 (CO) 10 (NCMe) 2 , 2b, or Os 3 (CO) 10 (l-H)(l-OH), 3, is employed instead. Triosmium-carboxylate clusters can be conveniently prepared by the reaction of 3 with the appropriate carboxylic acid in the presence of HBF 4 AE OEt 2 as an acid catalyst [8]. We have thus prepared a series of such triosmium-carboxylate clusters, 5, starting from the appropriate carboxylic acids, 4 (Scheme 2 and Table 1).…”
Section: Studies On the Incorporation Of Clusters Into Tamoxifenmentioning
confidence: 99%
“…For the synthesis of triosmium-carboxylate clusters, the parent triosmium carbonyl cluster Os 3 (CO) 12 , 1a, is of limited utility as it is rather inert; often an activated derivative such as Os 3 (CO) 10 (NCMe), 2a, Os 3 (CO) 10 (NCMe) 2 , 2b, or Os 3 (CO) 10 (l-H)(l-OH), 3, is employed instead. Triosmium-carboxylate clusters can be conveniently prepared by the reaction of 3 with the appropriate carboxylic acid in the presence of HBF 4 AE OEt 2 as an acid catalyst [8]. We have thus prepared a series of such triosmium-carboxylate clusters, 5, starting from the appropriate carboxylic acids, 4 (Scheme 2 and Table 1).…”
Section: Studies On the Incorporation Of Clusters Into Tamoxifenmentioning
confidence: 99%
“…All reagents were from commercial sources and used as supplied. The cluster Os 3 (m-H)(m-OH)(CO) 10 (1) was prepared according to the literature method [7].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that alkoxy-bridged triosmium clusters can be conveniently prepared from the cluster Os 3 (m-H)(m-OH)(CO) 10 (1) under mild conditions [7], and we have earlier successfully employed the methodology to anchor diols onto a triosmium cluster [1]. We were therefore interested in investigating whether we may be able to access the decacarbonyl derivative of 1-naphthol via this route.…”
Section: Introductionmentioning
confidence: 99%
“…b Values for 14a are averaged over the five crystallographically independent molecules; e.s.d.s are over the sample size of five molecules. (2) 2.8067 (10), Os(2)-Os (3) 2.8318 (10), Os (3)-Os (1) 2.8083 (10), Os(4)-Os(5) 2.8464(9), Os(5)-Os (6) 2.8413(9), Os (6) (17), S(2)-C(2) 1.791 (17), Os(1)-S(1)-Os (2) 70.23 (12), Os(4)-S(2)-Os(5) 72.11 (11). (2) 2.8708 (7), Os(2)-Os (3) 2.8746 (8), Os (3)-Os(1) 2.8450 (7), Os(4)-Os(5) 2.9244 (10), Os(5)-Os (6) 2.8659 (7), Os (6)-Os(4) 2.8758 (8), Os(1)-S(1) 2.418 (3), Os(2)-S(1) 2.426 (3), Os(4)-O(71) 2.131 (7), Os(5)-O(72) 2.150 (7), S(1)-C(1) 1.807 (10), Os(1)-S(1)-Os (2) 72.69 (8).…”
Section: General Proceduresmentioning
confidence: 99%
“…, 2067vs, 2058s, 2026vs, 2019s, 1999m, 1989m, 1983w 1029 (1028) Analyzer. The clusters [Os 3 (CO) 10 (l-H)(l-OH)], 1, and [Os 3 (CO) 10 (NCCH 3 ) 2 ], 2, were prepared according to reported procedures [11,12]. [Os 3 (CO) 12 ], 3a, and [Ru 3 (CO) 12 ], 3b, were purchased from Oxkem Ltd., and all other reagents were purchased from other commercial sources, and used as supplied without further purification.…”
Section: General Proceduresmentioning
confidence: 99%